2018
DOI: 10.1002/adsc.201800107
|View full text |Cite
|
Sign up to set email alerts
|

Chemoselective Synthesis of N‐arylbenzamides and Benzoyloxyacetanilides from Aryl Isocyanides: Styrene as Aryl and Arylcarboxymethylene Source

Abstract: Styrenes serve as unique aryl or arylcarboxymethylene source towards aryl isocyanides in the presence of Cu(II)/TBHP, and yield N-arylbenzamides or benzoyloxyacetanilides respectively. The chemoselectivity of the reaction is controlled by the nature of the substituents present on styrene ring. Whereas styrenes substituted with electronreleasing alkyl and alkoxy groups yield N-arylbenzamides, unsubstituted styrene and those with electron-withdrawing substituents furnish benzoyloxyacetanilides as the major produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…[28] Styrene also serves as an aryl or arylcarboxymethylene surrogate in the presence of Cu/TBHP. [29] Because of the vinylic hyperconjugation, it also undergoes ortho-para nucleophilic aromatic substitution. However, alkene typically reacts preferentially over the ring.…”
Section: Styrene: Chemistry and Metabolic Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…[28] Styrene also serves as an aryl or arylcarboxymethylene surrogate in the presence of Cu/TBHP. [29] Because of the vinylic hyperconjugation, it also undergoes ortho-para nucleophilic aromatic substitution. However, alkene typically reacts preferentially over the ring.…”
Section: Styrene: Chemistry and Metabolic Activationmentioning
confidence: 99%
“…Though styrene is a hydrocarbon, it is considered a functional group as its olefin can undergo deprotonation to form benzylic cation or benzylic radical [28] . Styrene also serves as an aryl or arylcarboxymethylene surrogate in the presence of Cu/TBHP [29] . Because of the vinylic hyperconjugation, it also undergoes ortho‐para nucleophilic aromatic substitution.…”
Section: Styrene: Chemistry and Metabolic Activationmentioning
confidence: 99%
“…In this context, styrenes substituted with electronreleasing alkyl and alkoxy groups and also benzylamines acted as aryl sources and react with aryl isocyanides to form N-arylbenzamides. 20 The reaction was catalyzed by Cu(OAc) 2 in the presence of tert-butyl hydroperoxide (TBHP). A Cu-catalyzed cross-coupling reaction of arenediazonium salts and isocyanides gave arenecarboxamides in moderate to good yields.…”
Section: Scheme 3 Mn(oac) 3 -Catalyzed Oxidative Coupling Reaction Ofmentioning
confidence: 99%
“…The reaction of styrenes and aryl isocyanides utilizing Cu(OAc) 2 and TBHP has a unique chemoselectivity giving benzoyloxyacetanilides 80 (Scheme 28). 20 A surprising point is that unsubstituted styrene and those with electronwithdrawing substituents act as an arylcarboxymethylene surrogate and give benzoyloxyacetanilides 80, while styrenes substituted with electron-releasing alkyl and alkoxy groups yield N-arylbenzamides (Section 2). Mechanistically, it was shown that the reaction proceeds by a radical…”
Section: Scheme 27 Alkylation Of Isocyanides With Peroxidesmentioning
confidence: 99%
“…4-(tert-Butyl)-N-(4-chlorophenyl)benzamide (3j). 36 Following the general procedure A, the title compound was prepared using 4-(tertbutyl)benzoic acid (1.2 equiv., 0.60 mmol, 106.9 mg) and 1-chloro-4nitrobenzene (1.0 equiv., 0.50 mmol, 78.8 mg) using petroleum ether/EtOAc (20:1) as an eluent to give the title compound as a white amorphous solid (79.9 mg, 56%). 1 H NMR (400 MHz, CDCl 3 ): δ 7.86−7.75 (m, 3H), 7.60 (d, J = 8.0 Hz, 2H), 7.50 (d, J = 7.7 Hz, 2H), 7.33 (d, J = 7.9 Hz, 2H), 1.35 (s, 9H).…”
Section: The Journal Of Organic Chemistrymentioning
confidence: 99%